Correlation of the Ga-68-bombesin analog Ga-68-BZH3 with receptors expression in gliomas as measured by quantitative dynamic positron emission tomography (dPET) and gene arrays - Strauss, Ludwig G.; Koczan, Dirk; Seiz, Marcel; Tüttenberg, Jochen; Schmieder, Kirsten; Pan, Leyun; Cheng, Caixia; Dimitrakopoulou-Strauss, Antonia (Molecular imaging & biology, 2012)
PurposeThe kinetics of Ga-68-BZH3, a Ga-68-bombesin analog, was compared to molecular biological data obtained from gene arrays in seven patients with a recurrent glioma. The primary aim of this study was the correlation of receptor expression and tracer kinetics.ProceduresDynamic positron emission tomography studies were performed and the data were analyzed by a volume-of-interest technique using a two-tissue compartment model as well as a non-compartment model. Gene array data were obtained from gene array analysis of tumor tissue samples.ResultsThe correlation analysis revealed a significant nonlinear correlation of r = 0.89 (p < 0.03) for k1 and BB2 (gastrin-releasing peptide receptor). BB1 and BB3 were not significantly correlated with k1. vb and k3 were not significantly correlated with the expression data of the receptors on the p < 0.05 level.ConclusionsThe parameter k1 is correlated with the expression of BB2 based on gene array data. The quantitative analysis of the Ga-68-BZH3 kinetics can be used to predict the receptor expression of BB2 in gliomas based on k1 of the compartment analysis. However, this study is limited to the expression data on the mRNA level and further studies are needed to assess the correlation of gene expression on the protein level.